Intrathecal Resiniferatoxin Modulates TRPV1 in DRG Neurons and Reduces TNF-Induced Pain-Related Behavior. (2nd August 2017) - Leo, M.; Schulte, M.; Schmitt, L.-I.; Schäfers, M.; Kleinschnitz, C.; Hagenacker, T.
Abstract : Transient receptor potential vanilloid-1 (TRPV1) is a nonselective cation channel, predominantly expressed in sensory neurons. TRPV1 is known to play an important role in the pathogenesis of inflammatory and neuropathic pain states. Previous studies suggest interactions between tumor necrosis factor- (TNF-) alpha and TRPV1, resulting in a modulation of ion channel function and protein expression in sensory neurons. We examined the effect of intrathecal administration of the ultrapotent TRPV1 agonist resiniferatoxin (RTX) on TNF-induced pain-associated behavior of rats using von Frey and hot plate behavioral testing. Intrathecal injection of TNF induces mechanical allodynia (2 and 20 ng/kg) and thermal hyperalgesia (200 ng) 24 h after administration. The additional intrathecal administration of RTX (1.9 μ g/kg) alleviates TNF-induced mechanical allodynia and thermal hyperalgesia 24 h after injection. In addition, TNF increases the TRPV1 protein level and number of TRPV1-expressing neurons. Both effects could be abolished by the administration of RTX. These results suggest that the involvement of TRPV1 in TNF-induced pain offers new TRPV1-based experimental therapeutic approaches and demonstrates the analgesic potential of RTX in inflammatory pain diseases.